Agrarian aspirations and demands as illustrated by the 1905 Royal Commission on Land Tenure : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University - Bailey, Ross Leonard (Massey University, 1972)
This essay is an examination of the 1905 Royal Commission report on Land Tenure. The introduction examines the Commission's final report and looks at its reception. The report and newspapers are set against each other in order to show what pressures were exerted on the Commission to come out in favour of the freehold. The essay also looks at the Minutes of evidence in order that themes not apparent in the final report can be examined. The aspirations and demands of witnesses are considered in relation to their background: rural and Urban, pro-freehold and pro-land nationalization. Newspapers and parliamentary debates are used where they comment or throw light on the evidence in the minutes and on the general issue of the freehold-leasehold controversy. The essay examines the idea that the freehold-leasehold controversy had a greater emotional dimension than a practical one. The practical side, however, has not been ignored. Two areas were selected for examination and were fairly representative of the problems throughout New Zealand. The conclusion suggests that the emotional aspect of the freehold-leasehold issue was largely a result of the agitation by freeholders, in order to preserve their way of life against the encroaching land nationalizers. The leaseholders were upset by the fear of having their rents revalued, and once this fear was removed most leasees-in-perpetuity were content with the lease-in-perpetuity system.
Keywords: New Zealand; Farmers; Land tenure